Novel technique of performing transbronchial lung cryobiopsy (TBLC) for diagnosing diffuse parenchymal lung diseases (DPLD) in infants. Issue 3 (6th February 2023) - Joseph, Tinku; Agrawal, Sumita; Nair, Sreeraj; Jayakumar, Chandrasekhara; Gopalakrishnan, Rajesh; Nambiar, Ajit
Abstract: Childhood interstitial lung disease (ChILD) diagnosis often requires surgical lung biopsy after the common causes are ruled out. However, surgical lung biopsy has its own set of complications. Hence transbronchial lung cryobiopsy has been used in various studies of adult interstitial lung disease (ILD) with good yield and minimal complications. But this newer mode is rarely used in diagnosing children with suspected ILD. Here, we present the first case of the use of this technique in an infant via a rigid tracheoscope. Abstract : Transbronchial lung cryobiopsy (TBLC) has been reported to have high diagnostic yield for adult interstitial lung disease (ILD) with limited complications. However, this technique has not been utilised for diagnosis of diffuse parenchymal lung diseases (DPLD) in an infant. We present the first case of infant lung cryobiopsy done using rigid tracheoscope in a suspected case of childhood interstitial lung disease.